2010
DOI: 10.1590/s0100-40422010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ni addition to a low-loaded palladium catalyst on the selective hydrogenation of 1-heptyne

Abstract: Recebido em 27/4/09; aceito em 30/10/09; publicado na web em 12/3/10 Semi-hydrogenation of alkynes has industrial and academic relevance on a large scale. To increase the activity, selectivity and lifetime of monometallic catalysts, the development of bimetallic catalysts has been investigated. 1-Heptyne hydrogenation over low-loaded Pd and Ni monometallic and PdNi bimetallic catalysts was studied in liquid phase at mild conditions. XPS results suggest that nickel addition to Pd modifies the electronic state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…The Ni-Pd/Al2O3 first peak is at the range of 100 to 200 °C which is due to the reduction of PdO and a second peak at the range of 300 to 600 °C which may be due to the reduction of NiAl2O4 species, which were formed by the diffusion of Ni 2+ into the support. The results is similar to those reported by Lederhos et al [22]. It can be observed that the presence of nickel shifted the peaks of NiO from 700 °C to lower temperature range, suggesting that the Ni-Pd/Al2O3 catalyst is easier to be reduced.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 11 (2supporting
confidence: 91%
“…The Ni-Pd/Al2O3 first peak is at the range of 100 to 200 °C which is due to the reduction of PdO and a second peak at the range of 300 to 600 °C which may be due to the reduction of NiAl2O4 species, which were formed by the diffusion of Ni 2+ into the support. The results is similar to those reported by Lederhos et al [22]. It can be observed that the presence of nickel shifted the peaks of NiO from 700 °C to lower temperature range, suggesting that the Ni-Pd/Al2O3 catalyst is easier to be reduced.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 11 (2supporting
confidence: 91%
“…Palladium is widely used in hydrogenation reactions due to its high hydrogenating capacity, being active and selective at low temperatures 19,34,35 . Overhydrogenation should however be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the high degree of sintering of the ruthenium metal particles could be due to the fact that, during the pretreatment process, no oxychlorinated species interacting with the support are formed, as noted earlier while studying ruthenium catalysts of different metal contents over the alumina support [12,21]. e low dispersion of nickel is a characteristic when this metal is used to prepare inorganic or carbonaceous catalysts [52,53].…”
Section: Catalysts and Support Characterizationmentioning
confidence: 55%